Mechanism of cholera toxin activation by a guanine nucleotide-dependent 19 kDa protein - Noda, Masatoshi; Tsai, Su-Chen; Adamik, Ronald; Moss, Joel; Vaughan, Martha (Biochimica et biophysica acta, 1990)
Cholera toxin causes the devastating diarrheal syndrome characteristic of cholera by catalyzing the ADP-ribosylation of G sα, a GTP-binding regulatory protein, resulting in activation of adenylyl cyclase. ADP-ribosylation of G sα is enhanced by 19 kDa guanine nucleotide-binding proteins known as ADP-ribosylation factors or ARFs. We investigated the effects of agents known to alter toxin-catalyzed activation of adenylyl cyclase on the stimulation of toxin- and toxin subunit-catalyzed ADP-ribosylation of G sα and other substrates by an ADP-ribosylation factor purified from a soluble fraction of bovine brain (sARF II). In the presence of GTP, sARF II enhanced activity of both the toxin catalytic unit and a reduced and alkylated fragment (‘A 1’), as a result of an increase in substrate affinity with no significant effects on V max. Activation of toxin was independent of G sα and was stimulated 4-fold sodiuim dodecyl sulfate, but abolished by Triton X-100. sARF II therefore serves as a direct allosteric activator of the A 1 protein and may thus amplify the pathological effects of cholera toxin.